Detection of parvovirus B19 and human herpesvirus 6 in pediatric dilated cardiomyopathy: Impact after heart transplantation - Bibhuti B Das; Bhupesh K Prusty; Jianli Niu; Meei-Li Huang; Haiying Zhu; Eva Eliassen; Jane M Kuypers; Keith R Jerome (Wolters Kluwer Medknow Publications, 2020)
Objectives: The aim of this study is to evaluate HHV-6 and PVB19 infection using polymerase chain reaction (PCR) and immunofluorescent assay (IFA) in the myocardium of pediatric patients with dilated cardiomyopathy (DCM) and the impact of viral persistence in the cardiac allograft after heart transplantation (HT). Methods: Multiplex droplet digital PCR was used to analyze the prevalence of viral sequences in myocardial samples from 48 pediatric DCM patients and 10 control subjects. Of the 48 DCM patients, 44 underwent HT. After HT, consecutive endomyocardial biopsy (EMB) samples were analyzed for the presence of PVB19 and HHV-6 antigens using IFA and the patients were evaluated for rejections, coronary vasculopathy, and graft loss. Results: Of the 48 DCM patients, 14 had positive viral PCR results in explanted/autopsy hearts. Among them, PVB19 was found in 8/48, HHV6 in 4/48, both PVB19 and HHV6 in 1/48, and enterovirus in one, but no adenovirus was found. The EMB samples obtained after HT were positive for PVB19 and HHV-6 in 7/44 and 3/44 cases, respectively. Viral presence in both the explanted heart and the cardiac allograft was demonstrated in 4 patients, 3 of whom were positive for PVB19, and one of whom was positive for HHV-6 pretransplant. Coronary vasculopathy and graft loss were more common in patients with PVB19-positive myocardial tissues versus those who were PVB19-negative. Conclusions: There is an association between PVB19 and HHV-6 infection and DCM in children. The study suggests the persistence of PVB19 and HHV-6 in the host can lead to subsequent viral reactivation in the transplanted heart, even in those recipients who do not have active myocarditis. PVB19 in the cardiac allograft tended toward higher adverse post-HT events.